2003
DOI: 10.1093/dnares/10.5.221
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Four Large Plasmids Harboring in a Unicellular Cyanobacterium, Synechocystis sp. PCC 6803

Abstract: The genome of the unicellular cyanobacterium Synechocystis sp. PCC 6803 consists of a single chromosome and several plasmids of different sizes, and the nucleotide sequences of the chromosome and three small plasmids (5.2 kb, 2.4 kb, and 2.3 kb) have already been sequenced. We newly determined the nucleotide sequences of four large plasmids, which have been identified in our laboratory (pSYSM:120 kb, pSYSX:106 kb, pSYSA:103 kb, and pSYSG:44 kb). Computer-aided analysis was performed to explore the genetic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 22 publications
1
106
0
Order By: Relevance
“…PCC 6803 were downloaded from NCBI, the Comprehensive Microbial Resource (CMR) of TIGR (http://www.tigr. org/CMR) and CyanoBase (http://genome.microbedb.jp/cyanobase/) (27). The Synechocystis sp.…”
Section: Construction and Analysis Of Knockoutmentioning
confidence: 99%
See 2 more Smart Citations
“…PCC 6803 were downloaded from NCBI, the Comprehensive Microbial Resource (CMR) of TIGR (http://www.tigr. org/CMR) and CyanoBase (http://genome.microbedb.jp/cyanobase/) (27). The Synechocystis sp.…”
Section: Construction and Analysis Of Knockoutmentioning
confidence: 99%
“…The Synechocystis sp. PCC 6803 genome contains 3569 predicted protein (27). The ratio between the mutant and the wild type was obtained directly based on the protein abundance for any given protein.…”
Section: Construction and Analysis Of Knockoutmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 7 plasmids in Synechocystis sp. PCC 6803 (Kaneko et al, 2003;Xu and McFadden, 1997;Yang and McFadden, 1993;Yang and McFadden, 1994) and 6 in Nostoc (also known as Anabaena) sp. PCC 7120 (Kaneko et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Three other twocomponent systems have been identified on the plasmids of Synechocystis sp. PCC 6803 (Kaneko et al, 2003), and they were shown not to be involved in the perception of hyperosmotic stress (Paithoonrangsarid et al, 2004). The real function of these plasmid-born two-component systems is yet to be explored.…”
mentioning
confidence: 99%